Sovereign risk and financial crises - Frenkel Michael; Karmann Alexander; Scholtens Bert (Berlin Springer-Verlag, 2004)
As the Asian economic crisis in the late 1990s revealed once again, financial crises are the rule rather than the exception in capitalist economies. The event also revealed that international public debt agreements are contingent claims. In a world of in
Keywords: Financial crisis; International finance; Risk management